Factors influencing preferences for real-time public transport information - CAULFIELD, BRIAN; O'MAHONY, MARGARET MARY (Association for European Transport, 2007)
This paper presents the results of a study undertaken in Dublin, to ascertain preferences for real-time public transport information. This study examines the need for public transport information across three stages of a public transport trip. The stages examined are as follows; stage one: pre-trip planning from home to work, stage two: at-stop/station information and stage three: pre-trip planning from work to home. At each of these stages the respondents were asked to choose between several methods of receiving information, via the internet, mobile phone, call centre or at stop real-time information displays. The study utilised a stated preference approach to ascertain what type of information is demanded at each stage and the willingness to pay amounts for this information. Specifically, this paper will focus upon the factors that influence the choice of real-time transport information option. Several factors from the literature have been proven to impact upon the utility derived from real-time public transport information. The results from this study are compared against the factors from the literature which have been proven to impact upon utility, to validate the findings of this study. The paper concludes with summary of the main findings of this study and how they contribute to the field of knowledge in this research area.
European Transport Conference: 2007: Leeuwenhorst, The Netherlands
PUBLISHED
Keywords: transport information - Dublin; public transport - Dublin